Seasonal changes in acceleration-speed profiles: Insights from soccer players across diverse age groups - Cardoso, P.; Tavares, F.; Loureiro, N.; Ferreira, R.; Araújo, J. P.; Sá Gomes, J.; Reis, J.; Vaz, J. R. (Sport Sciences for Health, 2025)
This study aimed to investigate the variation of the Acceleration-Speed (A-S) profile throughout one season in different age groups of elite young and professional soccer athletes. A total of 126 athletes from under-14 to B-team levels were analyzed in terms of their A-S profile, across a season divided in six training blocks. For all the blocks, we have calculated maximal theoretical acceleration (A0) and maximal theoretical speed (S0). Results revealed significant increases only in the S0 value for the under-15 age group (p < 0.05) during the season, while other age groups did not exhibit significant differences in the A-S profile over the same period. These findings emphasize the necessity of tailored training interventions to optimize acceleration and sprint capacities, particularly among younger players in the midst of physical development. Furthermore, the establishment of standardized norms tailored to different age groups based on these findings could facilitate the identification of outliers and inform individualized training strategies. This research could contribute to our understanding of the dynamic nature of sprinting performance and training demands in elite young soccer athletes, offering insights for optimizing performance outcomes and player development within soccer academies.